Color Engineering of Silicon Nitride Surfaces to Characterize the Polydopamine Refractive Index - Vega Moreno, Milena Amparo (2018)
A simple methodology to generate polydopamine (PDA) surfaces featured with color due to thin-film interference phenomena is presented. It is based on depositing ultra-thin films of polydopamine on a Si/Si 3 N 4 wafer that exhibits an interferential reflectance maximum right at the visible/UV boundary (∼400 nm). Therefore, a small deposit of PDA modifies the optical path, in such manner that the wavelength of the maximum of reflectance red shifts. Because the human eye is very sensitive to any change of the light spectral distribution at the visible region, very small film thickness changes (∼30 nm) are enough to notably modify the perceived color. Consequently, a controlled deposit of PDA, tune the color along the whole visible spectrum. Additionally, good quality of PDA deposits allowed us to determine the refractive index of polydopamine by ellipsometry spectroscopy. This data can be crucial in confocal skin microscopic techniques, presently used in diagnosis of skin tumors.